A coumarin-based reversible fluorescent probe for Cu2+ and S2− and its applicability in vivo and for organism imaging. (21st June 2021) - Lu, Wen; Shi, Jiuzhou; Chen, Jichao; Sun, Lu; Shao, Lingcen; Ren, Hongyu; Huang, Mengmeng; Wang, Yanqin; Yang, Shilong; Li, Xu
Abstract : A highly selective fluorescent probe was designed to detect Cu 2+ and S 2− in HeLa cells, zebrafish, and soybean root tissue. Abstract : This study describes the synthesis of a coumarin-based reversible fluorescent probe BuCAC for the detection of Cu 2+ and S 2− in CH3 CN : PBS (v/v = 8 : 2, pH = 7.4) solution. The resulting BuCAC exhibited high sensitivity (detection limit = 3.03 × 10 −7 M) and selectivity towards Cu 2+ through a 2 : 1 binding mode. In the presence of S 2−, the BuCAC–Cu 2+ recovered to BuCAC and CuS, which in turn perform the function of a sensitive probe with a lower detection limit of about 1.7 × 10 −7 M. This "on–off–on" process can easily occur in 1 min with a repetition of at least 5 times. The sensing mechanism was confirmed by Job's plot analysis, MS, and density theory calculation. Besides, fluorescence imaging in zebrafish, HeLa cells, and soybean root tissue revealed that the probe BuCAC could serve as a valuable tool for monitoring and tracking intracellular Cu 2+ and S 2− while benefiting from its excellent fluorescence performance and lower cytotoxicity.